Application of antenatal care with a holistic approach in reducing anxiety: - Fathia Rizki (Poltekkes Kemenkes Yogyakarta, 2022)
For pregnant women, anxiety often comes and gets heavier near labor, plus they now must live side by side with COVID-19. Therefore, holistic antenatal care, which is thorough physical, psychological, emotional, social, and spiritual care is needed. This research aims to determine the application of antenatal care with a holistic approach to reducing maternal anxiety. This research employs a mixed method. The sample for this quantitative research was pregnant women in their third trimester at the Sahabat Ibu dan Anak Cliniq in Bandung, totaling 80 women (case and control) who met the inclusion and exclusion criteria from June-September 2021. The data were collected using the HRS-A questionnaire. Meanwhile, the qualitative research sample was carried out by purposive random sampling. The results of qualitative data collection were given in a case report. The results showed that the application of antenatal care with a holistic approach had an effect in reducing maternal anxiety levels during the new normal with a p-value of 0.007<? (0.05). In addition, the results showed that pregnancy checks with a holistic approach made the mother's delivery experience better than those with the previous approach, made the mothers calmer and able to control emotions, and increased spiritual confidence. In conclusion, antenatal care with a holistic approach had an effect in reducing anxiety.